2022
DOI: 10.1007/s00432-022-04418-y
|View full text |Cite|
|
Sign up to set email alerts
|

Nanotechnology-augmented sonodynamic therapy and associated immune-mediated effects for the treatment of pancreatic ductal adenocarcinoma

Abstract: Purpose Sonodynamic therapy (SDT) is emerging as a cancer treatment alternative with significant advantages over conventional therapies, including its minimally invasive and site-specific nature, its radical antitumour efficacy with minimal side effects, and its capacity to raise an antitumour immune response. The study explores the efficacy of SDT in combination with nanotechnology against pancreatic ductal adenocarcinoma. Methods A nanoparticulate formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has been reported that sonoporation was successfully utilized to enhance nucleic acid delivery to neoplasms, skeletal muscle, and kidneys [128]. Sonoporation can be used with satisfactory results as a monotherapy or as an additional treatment option for inoperable or borderline resectable pancreatic ductal adenocarcinoma, as demonstrated in a study on ectopic murine pancreatic tumours [85]. For realizing minimally invasive cancer treatment, one study demonstrated the effectiveness and feasibility of drug delivery system-based SDT, which combined a small dose of NC-6300 and the low energy of HIFU in mouse models of pancreatic cancer [69].…”
Section: Sonodynamic Therapymentioning
confidence: 99%
“…It has been reported that sonoporation was successfully utilized to enhance nucleic acid delivery to neoplasms, skeletal muscle, and kidneys [128]. Sonoporation can be used with satisfactory results as a monotherapy or as an additional treatment option for inoperable or borderline resectable pancreatic ductal adenocarcinoma, as demonstrated in a study on ectopic murine pancreatic tumours [85]. For realizing minimally invasive cancer treatment, one study demonstrated the effectiveness and feasibility of drug delivery system-based SDT, which combined a small dose of NC-6300 and the low energy of HIFU in mouse models of pancreatic cancer [69].…”
Section: Sonodynamic Therapymentioning
confidence: 99%